Effect of yogic practices in the management of fibromyalgia: A review - Purnima Singh; Sobika Rao (Wolters Kluwer Medknow Publications, 2023)
Fibromyalgia (FM) is characterized by widespread pain, fatigue, stiffness, sleep irregularities, and tenderness of joints and muscles due to dysregulation of neurophysiological functions. It is more common in women compared to men. Till now, there is no specific treatment available for FM. The review aimed to review the literature on the effect of yogic practices on FM. The search was done in the following databases: Google Scholar and PubMed. The articles were searched using the keywords, FM, FM syndrome, Yoga, Pranayama, Yogic practices, and alternative therapy, without date restrictions which yielded 28 results, and eight articles were included in the final review. A review of the included articles showed the significant role of yogic practices in managing symptoms of FM, including stiffness, pain, sleep disturbance, fatigue, and depression. The yogic interventions such as asanas, Surya Namaskar, Nadi Shodhana Pranayama, and mindfulness meditation of specific duration were helpful in relieving the symptoms of FM. Yogic practices are helpful in the management of FM symptoms. Future randomized controlled trials contrasting various forms of yoga or exercise, however, will enable the identification of the most efficient treatments for FM and allow for more precise targeting of the patients who will benefit most from them.